Investors' Perception towards Investment Avenues - Paudel, Prabhat; Thapa, Kiran; Kandel, Sudarshan (Kalika Journal of Multidisciplinary Research, 2024)
The study aims to determine the factors influencing investors' perceptions toward various investment avenues in Nepal, focusing on the impact of risk, return, safety, tax benefits, and liquidity. Using a qualitative research design, content analysis was employed on 26 academic articles to identify key variables and their relationships with investment decisions. The primary variables investigated include risk perception, expected return, safety concerns, tax advantages, and liquidity preference. The findings reveal that younger investors exhibit a higher tolerance for risk, while older investors prioritise safety and stability. Metrics such as earnings per share (EPS), rate of return, and dividend per share (DPS) significantly influence investment decisions. The study also highlights the importance of liquidity, with investors favouring assets that can be easily converted into cash without significant loss. Additionally, perceptions of tax benefits and safety, particularly in fixed-income investments, play a crucial role in shaping investment choices. The discussion suggests that regulatory inconsistencies, limited financial instruments, and underdeveloped market infrastructure are key barriers to investment in Nepal. Despite these challenges, the study provides valuable insights for policymakers and financial institutions aiming to enhance market efficiency and attract more investment. Future research should focus on longitudinal studies and the influence of behavioural biases to deepen the understanding of investor behavior in Nepal.